2015
DOI: 10.1016/j.diabres.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restoring normoglycemia in type 1 diabetes on inflammatory profile and renal extracellular matrix structure after simultaneous pancreas and kidney transplantation

Abstract: Aims Patients with type 1 diabetes and end-stage renal disease with simultaneous pancreas and kidney (SPK) or kidney transplants alone (KA) were recruited 9–12 years post transplantation. We investigated differences between these groups with regard to inflammatory parameters and long-term structural changes in kidneys. Methods Blood samples were analyzed by ELISA and multiplex for chemokines, cytokines, growth factors, cell adhesion molecules and matrix metalloproteinases. Kidney graft biopsies were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
4
3
0
1
Order By: Relevance
“…Serum syndecan is increased in response to acute vascular trauma, as we have reported for syndecan-1 during coronary artery bypass surgery [17]. We have also shown that increased serum concentrations of syndecan-1 are related to early diabetic nephropathy [18], and we observed a trend for increased syndecan-1 serum concentrations in hyperglycemic individuals compared to normoglycemic kidney transplanted patients together with increased levels of the syndecan sheddase matrix metalloproteinase MMP-9 [19]. Furthermore, we have demonstrated high expression of syndecan-4 in endothelial cells [20], and in a case-cohort study including 1500 participants from the Tromsø study, we observed that serum syndecan-4 was an independent predictor of myocardial infarction [21].…”
Section: Introductionsupporting
confidence: 82%
“…Serum syndecan is increased in response to acute vascular trauma, as we have reported for syndecan-1 during coronary artery bypass surgery [17]. We have also shown that increased serum concentrations of syndecan-1 are related to early diabetic nephropathy [18], and we observed a trend for increased syndecan-1 serum concentrations in hyperglycemic individuals compared to normoglycemic kidney transplanted patients together with increased levels of the syndecan sheddase matrix metalloproteinase MMP-9 [19]. Furthermore, we have demonstrated high expression of syndecan-4 in endothelial cells [20], and in a case-cohort study including 1500 participants from the Tromsø study, we observed that serum syndecan-4 was an independent predictor of myocardial infarction [21].…”
Section: Introductionsupporting
confidence: 82%
“…Syndecan shedding is increased as a response to acute vascular trauma, as we have demonstrated for syndecan‐1 . We have also documented that increased serum syndecan‐1 is related to early diabetic nephropathy, and we observed a trend for increased syndecan‐1 serum levels in the hyperglycemic group compared to normoglycemic kidney transplanted patients together with increased levels of the syndecan‐1 sheddase MMP9 . This promising potential for syndecans as markers for endothelial dysfunction is further strengthened by our most recent results generated.…”
Section: Introductionsupporting
confidence: 80%
“…Moreover, several advanced glycation end-products were associated with plasma levels of MMP-2 and MMP-3 in T1D individuals [26]. Notably, in line with our present ndings, Reine et al described bene cial effects of successful SPK, as compared to KTA, on the kidney graft extracellular matrix structure in approximately 10-year observation in T1D patients [27]. We may hypothesize that the long-term restoration of normoglycemia results in favorable MMPs pro le, which probably re ects the slowing of vascular system damage (diabetic vasculopathy/remodeling).…”
Section: Discussionsupporting
confidence: 90%